Hospital Location Selection Targeting Indonesian NHI Patients for a Sustainable Business - Ireneus Ezra Tjitradi; Arviansyah Arviansyah (AFEBI Management and Business Review, 2021)
Finding an optimal location is a strategic decision, and an error of location judgment causes problems in the process and directly affects cost and profitability. Currently, Indonesian National Health Insurance (BPJS) program has high coverage growth in Indonesia; however, building hospitals targeting BPJS patients have faced some challenges and may lead to an unprofitable business. Therefore, location selection is a crucial aspect of a hospital’s operation, highly relates to profitability, and impacts business performance. Moreover, being profitable is not enough for businesses to survive in the long run; they have to be sustainable. The purpose of this study is to develop a reference for a location selection for healthcare management when building hospitals targeting BPJS patients. This paper utilizes the EGSEE framework for a sustainable business to evaluate comprehensive hospital location selection sub-factors. The study employs a systematic literature review and a modified Delphi method to examine the experts’ judgment. Finally, the Analytic Hierarchy Process is applied to develop the evaluation method. The result, social factor has the highest priority with a total weight of 42%, followed by economic factor (38%), and environment factor (20%). Besides hospital targeting BPJS patients have a sustainable business by being social, hospitals also contribute to increase the welfare of people living near the facility.